Programming Microsoft LINQ in Microsoft .NET Framework 4 - Pialorsi, Paolo (Microsoft ; O'Reilly [distributor], 2010)
Explains how to use LINQ (Language Integrated Query) while working with C♯ and Visual Basic, demonstrating practical applications for querying and managing data, the XML infoset, extending LINQ, and data binding.